Quantitative trait loci on chromosomes 9 and 19 modulate AII amacrine cell number in the mouse retina - Kulesh, Bridget; Bozadjian, Rachel; Parisi, Ryan J.; Leong, Stephanie A.; Kautzman, Amanda G.; Reese, Benjamin E.; Keeley, Patrick W. (Frontiers in Neuroscience, 2023)
Sequence variants modulating gene function or expression affect various heritable traits, including the number of neurons within a population. The present study employed a forward-genetic approach to identify candidate causal genes and their sequence variants controlling the number of one type of retinal neuron, the AII amacrine cell. Data from twenty-six recombinant inbred (RI) strains of mice derived from the parental C57BL/6J (B6/J) and A/J laboratory strains were used to identify genomic loci regulating cell number. Large variation in cell number is present across the RI strains, from a low of ∼57,000 cells to a high of ∼87,000 cells. Quantitative trait locus (QTL) analysis revealed three prospective controlling genomic loci, on Chromosomes (Chrs) 9, 11, and 19, each contributing additive effects that together approach the range of variation observed. Composite interval mapping validated two of these loci, and chromosome substitution strains, in which the A/J genome for Chr 9 or 19 was introgressed on a B6/J genetic background, showed increased numbers of AII amacrine cells as predicted by those two QTL effects. Analysis of the respective genomic loci identified candidate controlling genes defined by their retinal expression, their established biological functions, and by the presence of sequence variants expected to modulate gene function or expression. Two candidate genes, Dtx4 on Chr 19, being a regulator of Notch signaling, and Dixdc1 on Chr 9, a modulator of the WNT-β-catenin signaling pathway, were explored in further detail. Postnatal overexpression of Dtx4 was found to reduce the frequency of amacrine cells, while Dixdc1 knockout retinas contained an excess of AII amacrine cells. Sequence variants in each gene were identified, being the likely sources of variation in gene expression, ultimately contributing to the final number of AII amacrine cells.